Campus wide wireless messaging / Nurzeha Mohamad Zehni - Mohamad Zehni, Nurzeha (2014)
This project is aimed at designing the software to offer students the simplest way to communicate and exchange information with their lecturers without physically seeing them. For lecturer they can broadcast any news about class to students. The system will also enable the lecturer to store their time table and some information about them to students to access through user-friendly menu driven interface forms. This software is developed using Visual Basic 6.0 Enterprise Edition with Query based on Structured Query Language (SQL) and ActiveX Data Object (ADO) and Microsoft Access 2000 where the entire database is stored. Database can be accessed through Graphical User Interface (GUI).